2007
DOI: 10.2165/00044011-200727080-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissociative Experiences on Drug Treatment of Panic Disorder

Abstract: This study shows that dissociative experiences reduce the response to drug therapy in patients with panic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
5
18
0
Order By: Relevance
“…There is only one similar study we found in the literature which was performed by using Dissociative Experience Scale (DES) and Panic and Agoraphobia Scale (PAS). Patients in that study were divided into two groups with the same method and a significant decrease was found in the PAS scores of the group with low DES scores [26]. It might be caused by administration of alprazolam together with paroxetine for a certain period of time.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…There is only one similar study we found in the literature which was performed by using Dissociative Experience Scale (DES) and Panic and Agoraphobia Scale (PAS). Patients in that study were divided into two groups with the same method and a significant decrease was found in the PAS scores of the group with low DES scores [26]. It might be caused by administration of alprazolam together with paroxetine for a certain period of time.…”
Section: Discussionmentioning
confidence: 92%
“…No drugs other than venlafaxine were administered to the patients. There are several studies suggesting that dissociative symptoms have negative effects on response to the treatment of psychiatric disorders [26]. However, there is only one study investigating this effect within the context of pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High level of dissociation is typical for patients with borderline personality disorders 5,13 . The level of dissociation can be one of the reasons for treatment resistance in panic disorder patients [14][15][16] , as well as in the case of patients suffering from OCD [17][18][19] . Dissociation might be a predictor of negative treatment outcome in cognitive-behavioural therapy for patients with anxiety disorders 10 and obsessive compulsive disorder 20 .…”
Section: Introductionmentioning
confidence: 99%